Dynamic Buckling Analysis of Ductile Damage Evolution for Thin Shell With Lemaitre’s Model - Iheb Hammar; Mohamed Djermane; Belkacem Amieur (Salehan Institute of Higher Education, 2024)
Thin-shell structures are used in several fields of construction and are often exposed to severe dynamic environments, making them susceptible to dynamic instabilities. These instabilities are typically preceded by varying degrees of damage to the shell, justifying the need to incorporate this behavior in the formulation of the finite elements used. The objective of this work is to evaluate the different dynamic instability criterion in the presence of damage, afterward, evaluate the influence of this behavior on the stability of shells subjected to the dynamic excitations. The methodology of this project is essentially numerical, based on the finite element method. We are asked to program the introduction of damaging behavior and Lemaitre’s model criteria in the DYNCOQ program developed locally. To examine the results, two examples extracted from the literature were presented. The first model aimed to confirm the proper functioning of the program and the convergence of the plasticity criterion (Lemaitre's model). As for the second model, it allows us to test the dynamic instability. A comparison was made with experimental data from previously published literature, revealing a strong agreement between the calculated and experimental results. The obtained results prove the utility of considering this behavior in the shell analysis. Doi: 10.28991/CEJ-2024-010-03-012 Full Text: PDF